KRAS and NRF2 drive metabolic reprogramming in pancreatic cancer cells: the influence of oxidative and nitrosative stress - Rapozzi, Valentina; Comuzzi, Clara; Di Giorgio, Eros; Xodo, Luigi E. (Frontiers in Cell and Developmental Biology, 2025)
Cancer cells are subject to metabolic reprogramming, which leads to a sustained production of reactive oxygen species (ROS). Increased oxidative stress contributes to genomic instability and promotes malignant transformation. To counteract excessive ROS levels, cells activate nuclear factor erythroid 2–related factor 2 (NRF2), a key regulator of redox homeostasis that coordinates the transcription of a wide range of antioxidant and cytoprotective genes. This review examines the metabolic adaptations controlled by the KRAS–NRF2 axis under oxidative stress conditions. In addition, we highlight a novel function of NRF2 in regulating the expression of NOS2 by binding to a DNA enhancer element, thereby modulating the production of reactive nitrogen species (RNS). Finally, we discuss novel molecular strategies aimed at disrupting adaptive antioxidant responses in cancer cells and provide insights into combinatorial therapeutic approaches targeting redox balance in cancer.